2003
DOI: 10.1039/b305309a
|View full text |Cite
|
Sign up to set email alerts
|

Selective extraction of persistent organic pollutants from environmental matrices

Abstract: An attempt is made to determine the bioavailability of persistent organic pollutants (POP's) in environmental matrices. The approach is based on the use of the Hildebrand Solubility Parameter, and its individual parameters of hydrogen bonding, dispersion and polarity to select weak and strong solvents to extract POP's from soil matrices. The approach has been applied to both spiked soils and certified reference materials. Initial results indicate that it is possible to fractionate POP's from soil matrices base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Other researchers also used best solvent’s prediction tools such as the Hildebrand solubility parameters to learn about the optimal extraction solvent for organic compounds. Yet the predicted optimal solvents did often not perform best in practice, because Hildebrand parameters do not consider the influence of and interactions with the matrix and the analytes .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other researchers also used best solvent’s prediction tools such as the Hildebrand solubility parameters to learn about the optimal extraction solvent for organic compounds. Yet the predicted optimal solvents did often not perform best in practice, because Hildebrand parameters do not consider the influence of and interactions with the matrix and the analytes .…”
Section: Resultsmentioning
confidence: 99%
“…Other researchers also used best solvent’s prediction tools such as the Hildebrand solubility parameters to learn about the optimal extraction solvent for organic compounds. Yet the predicted optimal solvents did often not perform best in practice, because Hildebrand parameters do not consider the influence of and interactions with the matrix and the analytes . For instance, Brandli et al found dichloromethane 100% and hexane/acetone (1:3, v/v) to better extract PAHs from compost than toluene, for which absolute recoveries were only around 30%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approaches to assess the bioavailability of organic compounds are not as well defined as those for metals and a variety of approaches have been investigated including microbial degradation, [11][12][13] cyclodextrin extraction [14][15][16] and sequential extraction. [17][18][19] One similar approach for organic compounds, that has been used for metals, [7][8][9][10] is the in vitro gastrointestinal extraction procedure. In this case the in vitro gastrointestinal extraction procedure has been applied to assess the mobilisation of PAHs and PCBs into digestive fluids and to assess the bioavailability of these contaminants to humans.…”
Section: Introductionmentioning
confidence: 99%
“…Previously determined optimal conditions for extraction of POP's from soil were employed. 26 A certified reference material was analysed by Soxhlet extraction and by PFE in order to assess the quantitative extraction of these compounds from soil. Pressurised fluid extraction uses a smaller amount of solvent than Soxhlet and provides quicker extractions.…”
Section: Extraction Of Pop's Compounds From Soilmentioning
confidence: 99%